Peningkatan Hasil Belajar Sejarah Kebudayaan Islam Melalui Model Cooperative Learning Tipe Team Games Tournament (TGT) Di MTs Al-Quraniyah Bengkulu - Pasmah Chandra (AT-TAJDID, 2020)
The purpose of this study was to determine whether the application of the Teams-Games-Tournament (TGT) type of cooperative learning model could increase the activeness of the learning process in Al-Quraniyah Bengkulu MTs on the subject of khulafaurasyidin. To find out whether the application of the Teams-Games-Tournament (TGT) type of cooperative learning model can improve the learning outcomes of Grade VII students of Al-Quraniyah Bengkulu. This research is a Classroom Action Research (CAR) conducted in three cycles, each consisting of the stages of planning, action, observation, and reflection. The process of collecting data uses observation, interviews, tests, and documentation. Data is processed using quantitative data analysis. The results showed that the TGT type of cooperative learning model could increase student activity in SKI subjects in Al-Quraniyah Bengkulu MTs. This can be seen from the results of observations on the level of student activity in learning, showing that the average obtained from 9 aspects of student learning activeness in cycle I was 59.3% and increased to 67.55% in cycle II and increased again in the cycle III to 80.3%. Student SKI learning outcomes can be improved through the TGT type of cooperative learning model. Student learning test results show that students who reach KKM have increased from 50% in the first cycle, then increased to 62.5% in the second cycle and to 100% in the third cycle.